High-Performance O-Band Quantum-Dot Semiconductor Optical Amplifiers Directly Grown on a CMOS Compatible Silicon Substrate - Liu, Songtao; Norman, Justin; Dumont, Mario; Jung, Daehwan; Torres, Alfredo; Gossard, Arthur C.; Bowers, John E. (AMER CHEMICAL SOC, 2019)
High gain and high saturation output power silicon-based semiconductor optical amplifiers (SOAs) are essential elements in future large-scale silicon photonic integrated circuits (PICs) to compensate for the excess power penalties that are introduced by large numbers of passive components. We present here, for the first time, to the best of our knowledge, an O-band quantum-dot (QD) SOA that is directly grown on a complementary metal oxide-semiconductor compatible on-axis (001) silicon substrate. The QD-SOA demonstrates a > 100 nm gain bandwidth with an on-chip gain larger than 20 dB at 20 degrees C. A gain maxima of 39 dB occurs at the ground state peak wavelength with a 23 dBm saturation output power. P-modulation doping in the dot spacer layers is important to achieve higher gains (>20 dB) at high temperature (70 degrees C) with a 21 nm bandwidth. A fiber-to-fiber noise figure as low as 6.1 dB and a wall plug efficiency as high as 19.7% are also shown. The performance shows that the Si-based QD-SOAs can be important for Si PICs and employed under uncooled scenarios.
Keywords: LASERS; SI; PHOTONICS; SATURATION